Advocates, interest groups and Australian news coverage of alcohol advertising restrictions: content and framing analysis - Fogarty Andrea S; Chapman Simon (BMC, 2012)
Abstract Background Legislating restrictions on alcohol advertising is a cost-effective measure to reduce consumption of alcohol. Yet Australia relies upon industry self-regulation through voluntary codes of practice regarding the content, timing and placement of alcohol advertising. Ending industry self-regulation was recommended by the National Preventative Health Taskforce; a suggestion contested by the drinks industry. Debates about emerging alcohol-control policies regularly play out in the news media, with various groups seeking to influence the discussion. This paper examines news coverage of recommendations to restrict alcohol advertising to see how supporters and opponents frame the debate, with a view to providing some suggestions for policy advocates to advance the discussion. Methods We used content and framing analyses to examine 329 Australian newspaper items mentioning alcohol advertising restrictions over 24 months. All items were coded for mentions of specific types of advertising and types of advertising restrictions, the presence of news frames that opposed or endorsed advertising restrictions, statements made within each frame and the news-actors who appeared. Results Restrictions were the main focus in only 36% of 329 items. Alcohol advertising was conceived of as television (47%) and sport-related (56%). Restrictions were mentioned in non-specific terms (45%), or specified as restrictions on timing and placement (49%), or content (22%). Public health professionals (47%) appeared more frequently than drinks industry representatives (18%). Five supportive news frames suggested the policy is a sensible public health response, essential to protect children, needed to combat the drinks industry, required to stop pervasive branding, or as only an issue in sport. Four unsupportive frames positioned restrictions as unnecessary for a responsible industry, an attack on legitimate commercial activities, ineffective and 'nannyist', or inessential to government policy. Support varied among news-actors, with public health professionals (94%) more supportive than the public (68%), community-based organisations (76%), the government (72%), and the sports (16%), drinks (3%), or advertising (4%) industries. Conclusion Restrictions on alcohol advertising currently have low newsworthiness as a standalone issue. Future advocacy might better define the exact nature of required restrictions, anticipate vocal opposition and address forms of advertising beyond televised sport if exposure to advertising, especially among children, is to be reduced.